Risk of hepatitis B infection in pediatric acute lymphoblastic leukemia in a tertiary care center from South India. Issue 9 (4th May 2014) - Guruprasad, B.; Kavitha, S.; Aruna Kumari, B.S.; Vijaykumar, B.R.; Sumati, B.G.; Mahua, Sinha; Appaji, L.; Jayshree, R.S.
<x xml:space="preserve">Abstract</x> Background The prevalence of hepatitis B virus (HBV) infection is high in Asian countries. Little is known about outcome of leukemia in HBV infected patients in these regions. Hence, we conducted this study in two cohorts of patients. Procedure We retrospectively evaluated mortality, reduction in dose intensity and duration of therapy (intensive phase and maintenance phase) in children with acute lymphoblastic leukemia (ALL) who developed HBV infection. Sixty‐three patients with ALL were included in the retrospective cohort of the study. These were followed up for a minimum of 5 years. We prospectively investigated the prevalence of anti‐HBc antibodies in 105 treatment naïve pediatric patients with ALL and negative for HbsAg. Results Twenty of the 63 patients developed hepatitis, of which 10 were attributed to HBV. All the 10 patients with HBV hepatitis had significantly reduced dose intensity during maintenance therapy with an average delay in completion of therapy of 140 ± 83 days and also a high mortality (40%). In the prospective cohort of the study, 39% of treatment naive patients who were HBsAg negative were anti‐HBc positive at presentation, possibly reflecting occult HBV infection. Conclusions HBV infection poses a serious problem in patients with ALL. Hence we propose that in India, in addition to screening for HBsAg, patients with leukemia should also be screened for anti‐HBc. Improved hepatitis B vaccine coverage in the community under the universal immunization programme and introduction of HBV nucleic acid test (NAT) for blood donations should also help in addressing the problem. Pediatr Blood Cancer 2014;61:1616–1619. © 2014 Wiley Periodicals, Inc.